Implementation of Affirmative Action to Protect Women's Political Rights in the Regional People's Representative Council (DPRD) of Indragiri Hilir Regency - Muhammad Zulhidayat; Ferawati; Elmayanti (Journal of Law, Politic and Humanities, 2025)
Women's political rights are a centuries-long struggle. Women, who have often been considered second-class citizens, are struggling to gain the same rights as men in participating in political life. The struggle for women's political rights in Indonesia, including in Indragiri Hilir Regency, is an integral part of the history of the struggle for gender equality globally. Although there has been significant progress, there are still many challenges faced by women in accessing and exercising their political rights. Therefore, this research will discuss the urgency of women's political rights in the DPRD of Indragiri Hilir Regency in order to realise gender equality. Reasearch methods was Yudicial empiric methods. The results showed that women in the Regional People's Representative Council (DPRD) Indragiri Hilir Regency are very minimal, so this requires a new policy to provide space for women's representation in the Regional People's Representative Council (DPRD) Indragiri Hilir Regency. Although there is an increase in the number of women who occupy political positions, especially at the legislative level, the number of women's representation still does not reach the ideal target, as stated in Law Number 7 of 2017 concerning General Elections.